Mengaktualisasikan Astha Brata Dalam Konteks Krisis Kepemimpinan - Asep Yudha Wirajaya (Universitas Sebelas Maret, 2022)
Astha Brata is a leading power in the form of eight basic traits that must be ingrained for a leader and potential leader. Astha Brata personifies the power of the elements of the universe, such as sun, moon, stars, sky or sky, wind, ocean (water), earth, and fire. The symbolization of the value of leadership from the universe is converging on the process of self-awareness of a leader or potential leader to be able to appreciate nature in its entirety. The concepts and character of leadership based on local wisdom are still very relevant when applied by leaders or potential leaders at all levels. In fact, amid the rush of imported leadership theories, which are also not one hundred percent in harmony with the life of our nation and state, efforts to explore and re-actualize the concepts and noble values of Astha Brata's leadership are accurate concepts and foundations as well as the main saka guru that must be applied by a leader and potential leader. The concept of Astha Brata must always be applied, especially in dealing with situations and conditions that are